2007
DOI: 10.1371/journal.pone.0000698
|View full text |Cite
|
Sign up to set email alerts
|

Intense Sweetness Surpasses Cocaine Reward

Abstract: BackgroundRefined sugars (e.g., sucrose, fructose) were absent in the diet of most people until very recently in human history. Today overconsumption of diets rich in sugars contributes together with other factors to drive the current obesity epidemic. Overconsumption of sugar-dense foods or beverages is initially motivated by the pleasure of sweet taste and is often compared to drug addiction. Though there are many biological commonalities between sweetened diets and drugs of abuse, the addictive potential of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

30
472
2
17

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 513 publications
(521 citation statements)
references
References 73 publications
30
472
2
17
Order By: Relevance
“…In general, it appears that all natural rewards can be protective. Drug self-administration is reduced by the availability of a sweet such as saccharin or a glucose + saccharin mixture [83][84][85]. Drug self-administration is reduced by the availability of a running wheel, particularly in females [86].…”
Section: The Model: Drug Self-administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, it appears that all natural rewards can be protective. Drug self-administration is reduced by the availability of a sweet such as saccharin or a glucose + saccharin mixture [83][84][85]. Drug self-administration is reduced by the availability of a running wheel, particularly in females [86].…”
Section: The Model: Drug Self-administrationmentioning
confidence: 99%
“…Environmental enrichment also is protective in rats when provided during adulthood alone [90]. Sweets and even chow are protective when presented in adulthood concurrent with the opportunity to self-administer drug [83][84][85]. Finally, the sweets need not be concurrently available to be protective in adult rats.…”
Section: The Model: Drug Self-administrationmentioning
confidence: 99%
“…The recent tendency to eat over the necessary, with significant imbalances of the nutrients of the diet, has induced a higher incidence of eating disorders (ED). Especially, the excessive consumption of sugar-based foods has contributed, together with other environmental risk factors (dieting, media exposure, body image dissatisfaction, and weight-related teasing), to an increase of cases of over-eating diseases, such as obesity, binge-eating disorder, and bulimia nervosa [1][2][3][4]. Neuroscience focused the research strategies on the possibility that a maladaptive eating behavior can characterize some eating disorders as well as maladaptive drug intake characterizes drug addiction.…”
mentioning
confidence: 99%
“…It has been recognized that the resemblance may reflect the involvement of the same neural systems, including those implicated in regulatory self-control and reward in both groups of disorders. It has been widely demonstrated that the DAergic "meso-limbic" reward system has a crucial role not only in the passage from an occasional use to an abuse of drugs, but also in the transition from a normal feeding to a maladaptive compulsive eating behavior [1,3,[6][7][8]. Human studies showed that DAergic release correlates with the reward from both drug and food use [9,10].…”
mentioning
confidence: 99%
See 1 more Smart Citation